Yöunen pituuden, nukahtamisvaikeuden ja päiväväsymyksen muutos kaksivuotisessa verkkoelämäntapainterventiossa : tuloksia Muutosmatka-interventiosta - Mattsson, Maija (2024)
The purpose of this study was to examine the associations between sleep duration, difficulties falling asleep and daytime tiredness at the baseline, and changes in these variables during the lifestyle intervention for the participants in an online-based lifestyle intervention utilising acceptance and commitment therapy. A sufficiently long and good-quality sleep is essential for health. A healthy lifestyle reinforces a regular circadian rhythm and the conditions for good sleep. Sleep plays an important role in weight management. Insufficient sleep affects, among other things, the hormones that regulate hunger and feeling full. Sleep deprivation is also often reflected at a behavioural level, for example in reduced physical activity and changes in eating habits.